The Impact of Electronic Word-of-mouth on Gen Z Consumers’ Online Purchase Intention in E-Commerce Platforms: A Case Study in the Mekong Delta - Duy Vu Le (Migration Letters, 2023)
In the context of online shopping through e-commerce platforms, Electronic Word-of-Mouth (eWOM) plays a crucial role as a significant and unbiased source of information that many consumers rely on for decision-making. This research aims to examine the impact of eWOM on Gen Z consumers’ online purchase intention in the Mekong Delta market. The study integrates the Information Acceptance Model (IAM) and builds upon empirical research to investigate the relationship between eWOM and Gen Z consumers’ online purchase intention in e-commerce platforms. The Partial Least Squares Structural Equation Modeling (PLS SEM) technique is employed by the group of authors based on data collected from a survey involving 274 Gen Z individuals residing in the Mekong Delta region. The research findings highlight that the Quality of Information, Source Credibility, and Quantity of eWOM all have a positive and significant influence on the Acceptance of eWOM. Furthermore, the study establishes that the Acceptance of eWOM positively impacts Gen Z consumers’ Online purchase intention.